Wind effect on sediment suspensions over silt-dominated mixtures: An experimental study - Chen, Yongping; Pu, Jinshan; Zhu, Qin; Su, Min; Zhou, Zeng; Qiao, Zhongxing; Xu, Chunyang; Yao, Peng (Frontiers in Marine Science, 2023)
A series of laboratory experiments have been conducted to explore the wind effect on Sediment Suspended Concentrations (SSCs) in fine-grained coastal systems. The paddle waves were overplayed with surface-blowing winds in a wind-wave flume to mimic offshore swells coupling with local wind waves during rough weather. Both SSCs and water turbulences under different wind and wave conditions have been investigated over two kinds of sediment beds (Sediment 1, S1, D50 = 52µm and Sediment 2, S2, D50 = 90µm). The High Concentration Layers (HCL) were formed under most of the wave-only conditions, while with the introduction of the stronger wind, more sediment suspensions were transported upward, increasing SSCs in upper water elevations. The finer sediment S1 is easier to suspend than S2 under the same conditions. The enhancement of the vertical turbulence intensity (σw) by winds is the main reason for the increase in SSCs. Meanwhile, because the wind-induced turbulence can hardly penetrate the HCL, the turbulence intensities outside the HCL can be further amplified compared to the experiment without a sediment bed. The wind contributes over 65% of the SSC enlargement above the HCL under a wind of 10m/s for S1, while less than 20% inside the HCL in most wind conditions. The sediment mixing coefficient (ϵs), a crucial parameter for suspended sediment modeling, was enhanced with stronger winds. Although the existing formulas for the vertical distribution of ϵs are valid under both wave-only and small winds (2.5 m/s) for both sediment beds, the enhancement of ϵs caused by strong winds cannot be captured, requiring further research.